PENGARUH KEBIJAKAN INVESTASI, KEBIJAKAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN JASA YANG TERDAFTAR DI BURSA EFEK INDONESIA - HJ. ERVIVA FARIANTIN (GANEC SWARA, 2022)
The main goal of the company is to maximize shareholder wealth, this can be achieved by maximizing value of the company. This study aimed to determine the influence of Investment Policy, Financing Policy; And  Dividend Policy on Firm Value to service companies listed on Indonesia Stock Exchange. The research period was 2015-2020. The study used purposive sampling method in order to collect the sample. Population in this study was to all service companies go public in Bursa Efek Indonesia. Based on certain criteria, there were 12 of 86 service companies that matched with the sample. Data analysis technique uses classic assumption test: normality test, multicolonierity test, and heteroscedasticity test. Hypothesis test uses multiple regression analysis. Partially, the result of this research showed that investment policy have influence significant on firm value. While financing policy, and dividen policy not have significant influence on firm value.